Pengaruh Tepung Kedelai Kaya Isoflavon terhadap Testosteron Serum, Jumlah Sel Leydig dan Jumlah Sel Spermatogenik pada Tubuli Seminiferi Testis Tikus (Rattus norvegicus) - Sussi Astuti; Sutyarso Sutyarso (Universitas Atma Jaya Yogyakarta, 2010)
The objective of this experiment was to evaluate the effects of isoflavone-riched soybean flour with different levels of isoflavone on testosterone level, total Leydig cells, and total spermatogenic cells in the seminiferous tubules of male rats. Diet was given as isonitrogen and isocaloric with 10% of dietary protein from casein. Twenty five male of Sprague Dawley weaning rats (21 days old) were divided into five groups and treated with isoflavone-riched soybean flour by oral administration with different levels (dosages). The treatment was conducted for 2 months. The treatment of isoflavone-riched soybean flour with higher dosage of isoflavone increased the testosterone levels in the serum and the total Leydig cells in the seminiferous tubules of male rats. The optimum dosage of isoflavone was 1.5 mg/day resulted in the highest total spermatogenic cells of rat testes. The treatment isoflavone-riched soybean flour with 1.5 mg isoflavone/day on male rats resulted in the testosteron level of 2.96±0.45 ng/ml, total Leydig cells 70.22±9.34; while the number of spermatogonia, spermatocytes, early spermatids, late spermatids, and total spermatogenic cells were 48.44±4.82, 60.00±3.43, 221.56± 16.12, 164.33±17.94, and 494.33±32.94, respectively.